Cyanobacterial phycoerythrin purified from marine Lyngbya sp. induces apoptosis in lung carcinoma cells - Madamwar, Datta; Kaushal, Avani; Patel, Dipak K.; Desai, Swati N.; Upadhyay, Kapil; Devkar, Ranjitsinh (Bangladesh Journal of Pharmacology, 2015)
Phycoerythrins from various cyanobacterial sources have been extensively studied globally for their therapeutic potentials. This study shows the apoptotic potential of cyanobacterial phycoerythrin isolated, purified and characterized from marine Lyngbya sp. A09DM on human lung carcinoma cells (A549 cell). Results indicated that purified cyanobacterial phycoerythrin accounted for a dose-dependent decrement in cell viability, mitochondrial membrane potential and an increment in lactate dehydrogenase release. Higher dose of cyanobacterial phycoerythrin caused loss of cell viability and nuclear condensation/fragmentation. Flow cytometry accounted for more number of cells in G0/G1 phase and an increase in total number of early apoptotic cells (39.5%). Overall, this study is the first to report on apoptotic property of cyanobacterial phycoerythrin from marine Lyngbya sp. A09DM against A549 human lung carcinoma cells and requires a detailed scrutiny to establish its anti-cancer potential.